2012
DOI: 10.1074/jbc.m112.349803
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Curvature Protein Exhibits Interdomain Flexibility and Binds a Small GTPase

Abstract: Background: APPL2 is an endosomal Rab effector forming part of a signaling pathway linking cell surface and nucleus. Results: Crystal and solution structures of APPL2 were solved, and Rab partners were identified. Conclusion: APPL2 interacts tightly with Rab31, and APPL2 structures reveal unexpected domain motion that could have functional implications. Significance: APPL2 dynamics and interactions may be crucial for its cell signaling role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…This concurred with the binding of APPL2 to Rab31 found previously by yeast two-hybrid screening (King et al ., 2012). Both studies also show that APPL2 has a preference for binding to Rab31 over Rab5a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This concurred with the binding of APPL2 to Rab31 found previously by yeast two-hybrid screening (King et al ., 2012). Both studies also show that APPL2 has a preference for binding to Rab31 over Rab5a.…”
Section: Discussionsupporting
confidence: 92%
“…A yeast two-hybrid study showed that Rab31 preferentially binds to the complementary adaptor APPL2 (King et al ., 2012), although, to our knowledge, APPL2 has not previously been examined in phago­cytosis or in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…The final refined model contains 364 residues (a.a. 1–364) for one monomer and 361 residues (a.a. 1–361) for the other. The BAR domains within the dimer form a bundle that contains eight-helices, which is similar to the BAR domains of APPL1 and APPL2 (King et al, 2012; Li et al, 2007a; Zhu et al, 2007), but different from other reported BAR domains (Gallop et al, 2006; Peter et al, 2004; Pykäläinen et al, 2011; Shimada et al, 2007). The dimer interface has a large area (4100 Å 2 ), and contains mainly hydrophobic residues that likely mediate dimerization.…”
Section: Resultsmentioning
confidence: 65%
“…Therefore, the opposite effects of APPL1 and APPL2 on insulin-stimulated glucose uptake are attributed to the differential binding of these two adaptor proteins to Akt and TBC1D1. In line with these findings, APPL1 and APPL2 have been shown to bind to various types of Rab-GTPases involved in membrane trafficking (17,19). The binding of APPL1 and APPL2 to various sets of intracellular signaling molecules may be due to their differences in oligomerization, surface charges, and/or subcellular localization (17,18,31,32).…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, an in vitro study demonstrated that these two proteins possess distinct or even opposite functions in regulating glucose and lipid metabolism (16). Structural analysis revealed that APPL2 incorporates two homodimers, whereas APPL1 incorporates only one homodimer in the asymmetric unit (17)(18)(19). Although APPL1 binds to the adiponectin receptors and increases adiponectin-induced glucose uptake and fatty acid oxidation, APPL2 inhibits adiponectin actions in muscle cells (13,16).…”
mentioning
confidence: 99%